Bilateral Breast Reduction Without Opioid Analgesics: A Comparative Study. (3rd March 2017) - Parsa, Fereydoun Don; Cheng, Justin; Stephan, Brad; Castel, Nikki; Kim, Leslie; Murariu, Daniel; Parsa, Alan A
Abstract: Background: Breast reduction has traditionally been performed under general anesthesia with adjunct opioid use. However, opioids are associated with a wide variety of adverse effects, including nausea, vomiting, constipation, postoperative sedation, dizziness, and addiction. Objectives: This study compares bilateral breast reduction using a multimodal opioid-free pain management regimen vs traditional general anesthesia with adjunct opioids. Methods: A total of 83 female patients were enrolled in this study. Group 1 includes a retrospective series of 39 patients that underwent breast reduction via general anesthesia with adjunct opioid use. This series was compared to 2 prospective groups of patients who did not receive opioids either preoperatively or intraoperatively. In group 2, twenty-six patients underwent surgery under intravenous sedation and local anesthesia. In group 3, eighteen patients underwent surgery with general anesthesia. All patients in groups 2 and 3 received preoperative gabapentin and celecoxib along with infiltration of local anesthetics during the operation and prior to discharge to the Post-Anesthesia Care Unit (PACU). Primary outcome measures included the duration of surgery, time from end of operation to discharge home, postoperative opioid and antiemetic use, and unplanned postoperative hospitalizations. Results: When compared to group 1, groups 2 and 3 experienced a shorter time from end of operation to discharge home ( P < 0.05), fewer unplanned hospital admissions ( P < 0.05), and highly significant decrease in postoperative opioid use ( P < 0.001). Conclusions: This multimodal approach allows patients to safely undergo opioid-free bilateral breast reduction either under local or general anesthesia as an outpatient. This method resulted in significantly less morbidity, use of opioids postoperatively, as well as unplanned hospital admissions compared to "traditional" breast reduction under general anesthesia with the use of opioids. Level of Evidence: 3: